Early-Life Exposure to Non-Absorbable Broad-Spectrum Antibiotics Affects the Dopamine Mesocorticolimbic Pathway of Adult Rats in a Sex-Dependent Manner - González-Arancibia, Camila; Collio, Victoria; Silva-Olivares, Francisco; Montaña-Collao, Paula; Martínez-Pinto, Jonathan; Julio-Pieper, Marcela; Sotomayor-Zárate, Ramón; Bravo, Javier A. (Frontiers in Pharmacology, 2022)
Gut microbiota with a stable, rich, and diverse composition is associated with adequate postnatal brain development. Colonization of the infant’s gut begins at birth when parturition exposes the newborn to a set of maternal bacteria, increasing richness and diversity until one to two first years of age when a microbiota composition is stable until old age. Conversely, alterations in gut microbiota by diet, stress, infection, and antibiotic exposure have been associated with several pathologies, including metabolic and neuropsychiatric diseases such as obesity, anxiety, depression, and drug addiction, among others. However, the consequences of early-life exposure to antibiotics (ELEA) on the dopamine (DA) mesocorticolimbic circuit are poorly studied. In this context, we administered oral non-absorbable broad-spectrum antibiotics to pregnant Sprague-Dawley dams during the perinatal period (from embryonic day 18 until postnatal day 7) and investigated their adult offspring (postnatal day 60) to assess methylphenidate-induced conditioned place preference (CPP) and locomotor activity, DA release, DA and 3,4-dihydroxyphenylacetic acid (DOPAC) content in ventral tegmental area (VTA), and expression of key proteins within the mesocorticolimbic system. Our results show that ELEA affect the rats conduct by increasing drug-seeking behavior and locomotor activity induced by methylphenidate of males and females, respectively, while reducing dopamine striatal release and VTA content of DOPAC in females. In addition, antibiotics increased protein levels of DA type 1 receptor in prefrontal cortex and VTA of female rats, and tyrosine hydroxylase in VTA of adult male and female rats. Altogether, these results suggest that ELEA alters the development of the microbiota-gut-brain axis affecting the reward system and the response to abuse drugs in adulthood.